Palatabilitas Makanan Fungsional yang Mengandung Ekstrak Jintan Hitam (Nigella sativa) pada Kucing Domestik Bulu Pendek (Felis catus) - Kusumawati, Nina; Priosoeryanto, Bambang Pontjo; Esfandiari, Anita; Purwono, Rini Madyastuti; Kusumawati, Nina Tri (IPB University, 2024)
Plant extract is one of the functional ingredients to support health and immune system. Black cumin (Nigella sativa) is known to have a strong effect on immunomodulatory function. Its bitter taste and characteristic smell will affect the palatability of a final product. The palatability is important for product development in the pet food industry. The palatability defines cat’s preference and acceptance of a product. This research was aimed to determine the palatability of functional foods containing black cumin’s extract in domestic shorthair cats (Felis catus). The modified two bowl test was used in this study. Domestic shorthair cats aged 1-6 years, 7 spayed females and 2 neutered males, unvaccinated, and clinically healthy were participated in the study. Three bowls of food containing 89,1 mg; 222,75 mg; and 445,5 mg concentration of black cumin extract were offered to cats simultaneously. The first choice consumed, the duration of food consumed, and the amount of food intake were evaluated. A significant difference (p<0,05) was observed in the first choice consumed. The duration of food consumed, and the amount of food consumed were not found a significant difference. Based on all observations, this study indicates the food containing 222,75 mg concentration of black cumin is more palatable compared with other foods. The result of this study will be the foundation of the next research. Keywords: black cumin, cats, food, palatability